Penerapan Konsep Lean Manufacturing Untuk Meminimasi Waste Produksi Kerajinan Batik Kayu Pada Sanggar Seni Krebet - Davis Achriyandi Hisyammudin; Avesena Ahmad Aim Matim Ma’ruf; Muhammad Khoiri Muslim; Sumantri Safitra; Fauzi Al Asyroof; Ari Zaqi Al Faritsy (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Sanggar Peni in Krebet Hamlet produces various wooden batik crafts such as key chains, wooden spoons and forks, masks, statues, mirror frames, and other souvenirs. However, there are production layout issues that cause time wastage and lower efficiency. One example is the distance between production processes, such as from cutting to engraving which takes 86,520 seconds with a distance of 41 meters, and from engraving to sanding which takes 23,312 seconds with the same distance. Research using lean manufacturing methods, Current Value Stream Mapping (CVSM), Block Plan, and OMH revealed the time required at various stages of production. The cutting process required a total of 391.25 seconds (320 seconds for operation and 71.25 seconds for transportation), engraving 2,018.38 seconds (2,000 seconds for operation and 18.38 seconds for transportation), and sanding 763 seconds (752 seconds for operation and 10.83 seconds for transportation). The total material handling cost reaches Rp16,214 per day. Based on Block Plan analysis, the highest R-Score value of 0.95 indicates optimal efficiency in the arrangement of production facilities, which is expected to reduce time wastage and increase productivity on demand. Translated with DeepL.com (free version)